Rancang Bangun Jig & Fixture Untuk Pipe Fitting Steel Concentric Reducer Pada Mesin Bevel Pipa - Nurul Ulfah; Rahman Hakim; Michael Tri Adelitho (Jurnal Poli-Teknologi, 2020)
The development of manufacture Industries in the world rapidly increases especially in Indonesia. One of the manufacture industries is pipe fitting. PT Flo Bend Indonesia is the only manufacturer of pipe fitting steel and iron in Indonesia. The production process of pipe fitting is carried by the machining process. Quality of product produced by PT Flo Bend is depended on jig and fixture. Some of the problems that often appear are the variation of the material dimension that can disturb the beveling process. The time is needed to be longer to change the jig and fixture that suitable with material that needs to be cut. Therefore, this study was conducted to solve the problems by designing the jig and fixture that are more flexible and can adjust to the varying material dimension. The design focuses on the varying of concentric reducer size. Fishbone diagram was used to analyze the problems so that the approximate design concept can be determined. The result of FEM simulation shows 27,3 Mpa for the stress maximum and 8,1 for Factor of safety. Based on FMEA simulation, the design can reduce the time almost 600 minutes. In addition, the design can reduce the cost of the process. Therefore, it can be concluded that the design concept is safe to use.